Dynamic color generation with electrically tunable thin film optical coatings - Sreekanth, Kandammathe Valiyaveedu (2021)
Thin film optical coatings have a wide range of industrial applications from displays and lighting to photovoltaic cells. The realization of electrically tunable thin film optical coatings in the visible wavelength range is particularly important to develop energy efficient and dynamic color filters. Here, we experimentally demonstrate dynamic color generation using electrically tunable thin film optical coatings that consist of two different phase change materials (PCMs). The proposed active thin film nanocavity excites the Fano resonance that results from the coupling of a broadband and a narrowband absorber made up of phase change materials. The Fano resonance is then electrically tuned by structural phase switching of PCM layers to demonstrate active color filters covering the entire visible spectrum. In contrast to existing thin film optical coatings, the developed electrically tunable PCM based Fano resonant thin optical coatings have several advantages in tunable displays and active nanophotonic applications.